دراسة تأثير هجوم الثقوب السوداء على أداء بروتوكولات التوجيه AODVوOLSR في شبكات AD-HOC ذات الحمل المرتفع - صبيح, محمد (Latakia University Journal -Engineering Sciences Series, 2018)
إن شبكات الـ MANETs (Mobile Ad-Hoc Networks) اللاسلكية عبارة عن مجموعة من العقد اللاسلكية القادرة على الاتصال مع بعضها خلال الحركة والثبات، دون الحاجة إلى وجود أية نقاط دخول مركزية، أو بنية تحتية ثابتة. تعمل هذه العقد كموجهات قادرة على الحركة بحرية وبسرعات مختلفة. من مشاكل هذه التقنية، الضعف الأمني وحمايتها من الاختراق والهجمات، نتيجة عدم وجود نقطة تحكم مركزية قادرة على إدارة الاتصالات. هجمات الثقب الأسود هي واحدة من الهجمات الخطيرة التي تستهدف شبكات AD_HOC اللاسلكية من خلال نقطة مزيفة تستطيع امتصاص البيانات وارسالها إلى مكان آخر أو إهمالها. من هنا سندرس تأثير الثقب الأسود على أداء بروتوكول التوجيه التفاعلي AODV وعلى بروتوكول التوجيه غير التفاعلي OLSR من اجل عدد متغير من العقد المتحركة بسرعات مختلف في بيئة ذات حمل عال. MANET is a set of wireless nodes that can communicate with each other through movement and stability, without the need for the existence of any central entry points, or fixed infrastructure. These nodes operate as routers, which are able to move freely with different speeds. These networks suffer from weaknesses such as poor security and protection against intrusion attacks because a central control point that manages communications among nodes does not exist.Black hole attack is one of the most serious attacks that target Ad-HOC networks through a false point that can neglect or absorb the data and send it to another place Hence, we investigate the influence of the black hole attack on the performance of interactive routing protocol AODV and the non-interactive OLSR for a variable number of nodes moving with different speeds in a high load environment.